Nonlinearity of 3 minute Slow Magnetoacoustic Waves in the Sunspot Umbral Atmosphere - Y. Sanjay; S. Krishna Prasad; Robert Sych; P. S. Rawat (The Astrophysical Journal)
Slow magnetoacoustic waves with a 3 minute period are upward-propagating waves traveling through the density-stratified umbral atmosphere. The decreasing density causes their amplitude to increase, developing into nonlinear waves through steepening and eventually forming shocks. To investigate the vertical evolution of this wave nonlinearity, we utilized multiwavelength data from the Atmospheric Imaging Assembly (AIA) onboard the Solar Dynamics Observatory, covering from the photosphere to the lower corona across 20 active regions. The steepening of the wave profile leads to the generation of higher harmonics. We quantify this using a nonlinearity index (NI), defined as the ratio of the amplitude of the second harmonic to the fundamental obtained using wavelet analysis. We find a characteristic pattern: nonlinearity increases from the photosphere through the lower chromosphere, peaking near the AIA 1700 Å formation height, and decreases at higher altitudes, notably in the AIA 304 Å channel. This trend indicates progressive wave steepening and subsequent energy dissipation before reaching the formation of AIA 304 Å, consistent with shock formation in the lower atmosphere. An additional rise in NI is observed at the AIA 131 Å channel, followed by a decline in AIA 171 Å, suggesting a second phase of wave nonlinearity evolution in the lower corona. Based on the NI profile and the formation heights of these channels, we conjecture that nonlinear wave processes are most prominent between the AIA 1700 Å and AIA 304 Å formation layers and again between AIA 131 Å and AIA 171 Å.